Biosynthesis and Pharmacological Activities of the Bioactive Compounds of White Mulberry (Morus alba): Current Paradigms and Future Challenges - Fatima M.; Dar M.A.; Dhanavade M.J.; Abbas S.Z.; Bukhari M.N.; Arsalan A.; Liao Y.; Wan J.; Shah Syed Bukhari J.; Ouyang Z. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Traditional natural products have been the focus of research to explore their medicinal properties. One such medicinally important plant is the white mulberry, Morus alba, widely distributed in the Asian subcontinent. It is one of the most cultivated species of mulberry tree and has attracted more focus from researchers because of its abundance in phytochemicals as well as multipurpose uses. The leaves, fruits and other parts of the white mulberry plant act as a source of valuable bioactive compounds like flavonoids, phenolic acids, terpenoids and alkaloids. These secondary metabolites have manifold healthy uses as they possess antioxidant, anti-inflammatory, antidiabetic, neutrotrophic, and anticancer properties. Despite the increasing scientific interest in this plant, there are very few reviews that highlight the phytochemistry and biological potential of white mulberry for biomedical research. To this end, this review elaborates the phytochemistry, biosynthetic pathways and pharmacological activities of the glycoside flavonoids of Morus alba. A comprehensive analysis of the available literature indicates that Morus alba could emerge as a promising natural agent to combat diverse conditions including diabetes, cancer, inflammation and infectious diseases. To achieve such important objectives, it is crucial to elucidate the biosynthesis and regulation mechanisms of the bioactive compounds in white mulberry as well as the multifaceted pharmacological effects attributed to this plant resource. The present review paper is intended to present a summary of existing scientific data and a guide for further research in the phytochemistry and pharmacology of white mulberry. Further, a biosynthetic pathway analysis of the glycoside flavonoid in mulberry is also given. Lastly, we discuss the pros and cons of the current research to ensure the prudent and effective therapeutic value of mulberry for promoting human and animal health. ? 2024 by the authors.